The Politeness Strategies Utilized by Postgraduate Students and Lecturers in Asynchronous online-learning Discussion - Ni kadek Citrawati; Ni Luh Putu Sri Adnyani; Ni Nyoman Padmadewi; Ni Komang Arie Suwastini (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
Politeness strategies are essential to communicate with others, either face-to-face or using computer-mediated communication synchronously or asynchronously. The advancement of technology also contributes to the development of the communication strategy. The study pointed at examining the politeness strategies utilized by students and teachers in an asynchronous online discussion. It used qualitative designed. The participants were 24 postgraduate students at a state university in North Bali. The data were gathered from the asynchronous online discussion on New Direction in ELT and Bilingual and Bilingual Education course. The study found that positive politeness is primarily used in the discussion. The result showed that the lecturers and students had a great awareness to apply politeness strategies in communicatio